2006
DOI: 10.1097/01.bpb.0000186643.99568.35
|View full text |Cite
|
Sign up to set email alerts
|

Supramalleolar osteotomy for unilateral tibial torsion

Abstract: Surgical correction of unilateral torsional deformity of the tibia is indicated in fewer than 1% of cases. Treatment is limited to those who have a progressive deformity, who are symptomatic and on whom conservative treatment has failed. We present the results of an osteotomy performed at the supramalleolar level leaving the fibula intact and held with staples. In 7 years, 13 children with a mean age of 13.4 years (range 10-16 years) underwent osteotomy. Six osteotomies were performed for internal tibial torsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…With regard to tibial torsion, surgery generally been avoided for patients younger than 8 years of age 3,105,120,121 .…”
Section: Operative Considerationsmentioning
confidence: 99%
“…With regard to tibial torsion, surgery generally been avoided for patients younger than 8 years of age 3,105,120,121 .…”
Section: Operative Considerationsmentioning
confidence: 99%
“…Wiltse described closing medial wedge supramalleolar osteotomy to realign the ankle in valgus deformity [28]. Others, such as Lloyd-Roberts, Lichtblau, McNicol, and Goldner, used supramalleolar osteotomy to correct equinus and derotate the tibia in equinovarus deformities [4,5,7,9,11,14,16,20,24,[29][30][31][32]. Abraham utilized the approach to correct ankle valgus in patients with myelomeningocele [2].…”
Section: Discussionmentioning
confidence: 99%
“…Pearce presented a small series of hemophilic arthropathy patients treated for valgus deformity by supramalleolar osteotomy [18]. Many authors have utilized supramalleolar osteotomies to derotate the tibia alone in torsional deformities [4,5,7,9,11,14,16,20,24]. Percutaneous supramalleolar osteotomies have been performed for rotational deformities in cerebral palsy [9].…”
Section: Discussionmentioning
confidence: 99%
“…Our retrospective study proved that the mean time to radiographic consolidation in the WF group was as short as 7.2 weeks. Savva et al reported a mean time to union of 12 weeks after unilateral SMO stabilized with staples [22]. Nevertheless, the authors did not specify their definition of "union," and this was no primary endpoint in their study.…”
Section: Time To Radiographic Consolidationmentioning
confidence: 98%